VALIDATED DISSOLUTION METHOD FOR SIMULTANEOUS ESTIMATION OF TAMSULOSIN HCL AND TADALAFIL TABLET DOSAGE FORM USING RP-HPLC - CHARUSHILA BHANGALE,; RUPALI KALAMBE,; KAVERI VADITAKE, (The Bioscan, 2025)
Testing for drug dissolution is a crucial step in pharmaceutical development and continuous quality control of medication release characteristics. Drug in-vitro behaviour has been effectively described using profiles obtained from dissolution rate experiments. The current work addresses the development and validation of RP-HPLC for the detection of Tadalafil and Tamsulosin HCL in tablet and bulk drug formulations, as well as its use in in-vitro dissolving studies. Chromatography was carried on Bakerbond C18 (250 mm X4.6 ID) having particle size 5 micron the analytical coloum using Mobile phase pH 6.8 Phosphate buffer :Acetonitrile (70:30 v/v) at a flow rate 0.8 ml/min. The detection was carried out at wavelength 244 nm. Tamsulosin HCL and Tadalafil were shown to have retention times of 2.8 and 4.5 minutes, respectively. 0.1 N HCl dissolving Medium was used to analyse the dissolving pattern.A time point of 45 minutes was selected, and a USP Type I apparatus was employed with 100 RPM. For Tamsulosin HCL, the correlation coefficient was 0.9994, while for Tadalafil, it was 0.9974. Regarding linearity, accuracy, precision, robustness, ruggedness, specificity, and system applicability, the proposed approach was found to be valid. The recovery rate was determined to be between 99.63 and 101.04%. The method employed was specific for the identification and quantification of tadalafil and tamsulosin HCL in samples of dissolution and was accurate, precise, and linear over the analytical range.